(untitled) (MAUSAM, 2025)
This study presents column integrated AOD readings from satellites and from fourteen sunphotometers in southeast Asia. The comparison result shows that AOD estimated from Aqua satellite and sunphotometeris in reasonable agreement with the measurement, with RMSE of 0.09–0.42 for monthly cases. The AOD obtained by comparing data from the OMI with those obtained from sunphotometer observations was found to be of good agreement, with a RMSE of 0.27 and MBE of –0.01. The study presents AOD resource maps generated by GIS, Kriging (Geographic Information System) utilizing OMI data for 16-year period 2005–2020. The seasons for southeast Asia are defined as summer (March-May) and winter (June–February).According to upper southeast Asia seasonal patterns, the AOD was higher and reached its maximum in the summer but was lower and reached its minimum in winter. In the case of lower southeast Asia, the AOD was maximum in the winter but was minimum in summer. The maps reveal that geographic characteristics of eleven countries and the tropical monsoons had a significant impact on regional distribution of AOD. This work presents a model for determining AOD using organic carbon and black carbon from MERRA-2 and specific humidity from GLDAS. The model was created to estimate daily AOD (R = 0.71) and monthly AOD (R = 0.83) based on 5-year (2012–2016) AOD data from these stations, and independent data were used to validate for the 4-year period (2017 to 2020). It can be seen that values of monthly AOD predicted by the model had an RMSE of 0.20. The model2 monthly AOD (R = 0.94) was developed using visibility (195 meteorological stations) and angstrom expernent (Aqua) to enable the estimation of AOD. When compared to an independent data set, this model2 performs reasonably, with RMSE and MBE of 0.23 and –0.01, respectively.